ANALISIS PENGARUH KEPUASAN PELAYANAN PELANGGAN TERHADAP KINERJA BANK PADA PT BANK DAGANG NEGARA (BNI) CABANG PALANGKA RAYA - Pamungkur, Pamungkur; Sunarmie, Sunarmie (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
Abstract, This study aimed (a) to analyze the conformity between interest level of service components according to customers with the performance done by Bank Negara Indonesia (BNI) and (b) to analyze customers satisfaction on services provided so as to contribute the performance of Bank Negara Indonesia (BNI) to achieve good quality improvement by the stipulation of main priority. Qualitative data by scoring in calculation scale. A statement or question requiring alternative response, such as: very satisfied, satisfied, less satisfied, not satisfied at all, respectively with figures given 4 (four), 3 (three), 2 (two), and 1 (one). Study results suggested that factors becoming main priority or at Quadrant IV on cartesius diagram that should be performed as customers expectation among others: Teller attention to customers, all employees’ integrity in terms of servicing customers, waiting time in ATM queue, the presence of ATM machine, Interest Rate given by bank currently.